Historical-juridical notes on the duty to provide alimony/child support in the medieval juridical doctrine* (Italian Review of Legal History, 2019)
The essay underlines that the Corpus iuris civilis prescribed that every parent had the duty to provide alimony for his children, but children born ex incestuous vel damnato coitu did not enjoy this kind of support. The medieval scholars have studied in depth this topic and have analyzed the case of breastfeeding up to three years and the one concerning the regulation of that duty in case of separated parents. For what regards adulterine children, civilians followed the Justinian law, until the moment a Decretale, included in the Liber Extra, predicting this duty remained in force.  In the following period, the canonists have maintained the child allowance duty even for adulterine ones.  Civil law scholars did not share the same approach up to the period of the school of commentators. The legal obligation to pay alimony included also the duty to provide the tectum and the educatio. Education was considered according to the economic and social conditions of the family.In the appendix, the contribution includes some memories of the childhood of the author during the period 1947-1950.
Keywords: Child; Alimony; Justinian's law